2023
DOI: 10.3389/fenrg.2023.1114230
|View full text |Cite
|
Sign up to set email alerts
|

Application of signal processing techniques and intelligent classifiers for high-impedance fault detection in ensuring the reliable operation of power distribution systems

Abstract: High-impedance fault (HIF) is always a threat and the biggest challenge in the power transmission and distribution system (PTDS). For a PTDS to operate effectively, HIF diagnosis is essential. However, given the HIF’s nature and the involved complexity, detection, identification, and fault location are difficult. This will be even more complicated in conventional PTDSs as they are inefficient and highly vulnerable. Given the importance and urgent need for HIF diagnosis in PTDS, this study reviews state-of-the-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…A literature review has shown that combining multiple functions in one microprocessor terminal dramatically reduces the reliability of protection, since if this terminal fails, too many functions will be lost at once compared to the case when these functions are distributed among several terminals [6]- [9], the need to limit the number of functions implemented in one terminal was also discussed in their reports by scientists at the international conference "modern trends in the development of protection systems and automation of power systems" [10]- [12], a sharp increase in the level of complexity of the work of personnel servicing protection with the transition to the MPD, as the cause of severe accidents in power systems [13], [14], the complexity of the software interface and the need to introduce an excessive number of set points during the programming of the MPR [15]- [17], the unsatisfactory state of the electromagnetic environment at most old substations, which were designed and built for electromechanical protection [18]- [20], and not for microprocessor protection [21], and about the numerous failures in the operation of the MPD arising from this [22], the lack of universal strict requirements for the hardware of the MPD and software, and as a result [23], too many programs and algorithms embedded in the MPD used in one power system, which leads to problems during operation and to increase the probability of false operation of these devices. Most of these devices must be installed in heated switchgear, since at temperatures below -25 degrees, the liquid crystal display with which microprocessor devices are equipped becomes unreadable.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review has shown that combining multiple functions in one microprocessor terminal dramatically reduces the reliability of protection, since if this terminal fails, too many functions will be lost at once compared to the case when these functions are distributed among several terminals [6]- [9], the need to limit the number of functions implemented in one terminal was also discussed in their reports by scientists at the international conference "modern trends in the development of protection systems and automation of power systems" [10]- [12], a sharp increase in the level of complexity of the work of personnel servicing protection with the transition to the MPD, as the cause of severe accidents in power systems [13], [14], the complexity of the software interface and the need to introduce an excessive number of set points during the programming of the MPR [15]- [17], the unsatisfactory state of the electromagnetic environment at most old substations, which were designed and built for electromechanical protection [18]- [20], and not for microprocessor protection [21], and about the numerous failures in the operation of the MPD arising from this [22], the lack of universal strict requirements for the hardware of the MPD and software, and as a result [23], too many programs and algorithms embedded in the MPD used in one power system, which leads to problems during operation and to increase the probability of false operation of these devices. Most of these devices must be installed in heated switchgear, since at temperatures below -25 degrees, the liquid crystal display with which microprocessor devices are equipped becomes unreadable.…”
Section: Introductionmentioning
confidence: 99%